Pengaruh Good Corporate Governance, Corporate Social Responsibility & Kinerja Keuangan terhadap Nilai Perusahaan - -, Wardoyo; Veronica, Theodora Martina (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2013)
The purpose of this study is to know and analyze the effect of Good Corporate Governance (by looking at the number of commissioners, the independence of commissioners board, board size, and the number of audit committee members), corporate social responsibility and corporate performance (ROA and ROE) on firm value. The objects of study are all of go public banking companies. There are 29 banks actually. However, the samples are only 24 banks. They were chosen based on the observation of data completeness done from 2008 to 2010. The independent variables are GCG, CSR, and corporate performance, while the dependent variable is firm value which is measured by using Tobins Q. The data analysis applied for this study is correlation analysis, determination analysis, t test, f test, and multiple linear regression analysis. The result shows that the size of directors board, ROA and ROE have significant influences on the company value; while the board size, board independence, the number of audit committee members, and corporate social responsibility do not have significant effect on firm value.